2019
DOI: 10.5943/ajom/2/1/13
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization, distribution and ecology of four species of Amanita from north-western Himalaya, India

Abstract: Four species of Amanita namely; A. concentrica, A. flavipes, A. fritillaria and A. avellaneosquamosa are described from North-western Himalaya, India. Morphological details and illustrations are given here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The genus Amanita Pers. ( Amanitaceae ) have recently earned considerable attention, with new records and novel species being described from India (Bhatt et al 2003, Semwal et al 2005, 2020, Das et al 2017, Tibpromma et al 2017, Hosen et al 2018, Mehmood et al 2018a, b2018b, c2018c, 2019, Phookamsak et al 2019). To date, the genus Amanita is comprised of 613 validly published species from all over the world (Tulloss and Yang 2021) and about 66 species have been reported from India (Das et al 2017, Hosen et al 2018, Mehmood et al 2018a, b2018b, c2018c, d2018d, Kumar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Amanita Pers. ( Amanitaceae ) have recently earned considerable attention, with new records and novel species being described from India (Bhatt et al 2003, Semwal et al 2005, 2020, Das et al 2017, Tibpromma et al 2017, Hosen et al 2018, Mehmood et al 2018a, b2018b, c2018c, 2019, Phookamsak et al 2019). To date, the genus Amanita is comprised of 613 validly published species from all over the world (Tulloss and Yang 2021) and about 66 species have been reported from India (Das et al 2017, Hosen et al 2018, Mehmood et al 2018a, b2018b, c2018c, d2018d, Kumar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So far, only three species of sect. Amidella , namely Amanita avellaneosquamosa (S.Imai) S.Imai, A. clarisquamosa (S.Imai) S.Imai and A. pseudorufobrunnescens Semwal et al have been reported from India (Bhatt et al 2003, Semwal et al 2005, 2020, Mehmood et al 2019).…”
Section: Introductionmentioning
confidence: 99%